A princess in the kingdom of domination - Chartrand, Gary; Henning, Michael A.; Zhang, Ping (Utilitas Mathematica, 2014)
A dominating set in a graph G is a set S of vertices of G such that every vertex not in S is adjacent to a vertex of S. The domination number of G is the minimum cardinality of a dominating set of G. In this paper, we survey contributions to domination theory in graphs by Teresa W. Haynes.